Epstein-Barr virus and human diseases: recent advances in diagnosis. - Okano, M (1988)
Since the discovery of Epstein-Barr virus (EBV) from a cultured Burkitt's lymphoma cell line in 1964, the virus has been associated with Burkitt's lymphoma, nasopharyngeal carcinoma, and infectious mononucleosis. During the recent decade, EBV has been etiologically implicated in a broad spectrum of human diseases. The precise role of this virus in these diseases is not well understood, but clearly, defective immunosurveillance against the virus may permit an uncontrolled proliferation of EBV-infected cells. As a result, a growing number of cases of EBV-associated B-cell proliferative diseases or lymphoma have been noted in patients with primary and acquired immunodeficiencies. These lymphoproliferative diseases and others, such as chronic mononucleosis syndrome, are leading to new areas of investigation which are providing information regarding the pathogenetic mechanisms of EBV-induced diseases. The early accurate diagnosis of EBV infection can be achieved by performing EBV-specific serology, detecting for EBV-determined nuclear antigen in tissues, establishing spontaneous lymphoid cell lines, and using molecular hybridization techniques for demonstrating the presence of viral genome in affected lesions.